Does Self-Efficacy Moderate the Effect of Customer Incivility on Work Engagement? - Wisesa, I Made Siddhi; Rahyuda, Agoes Ganesha (International Research Journal of Business Studies, 2024)
This research aims to determine how customer incivility can impact frontlines’ work engagement and how self-efficacy moderates the relationship between customer incivility and frontlines’ work engagement. This research uses a saturated or census sampling technique, which is included in non-probability sampling with a sample of 70 participants. The data for this research is obtained through questionnaires and interviews. This research uses Moderated Regression Analysis (MRA) using the Statistical Package for the Social Sciences (SPSS). Research analysis shows that customer incivility can reduce the level of work engagement of frontline employees. A high level of self-efficacy can maintain or increase the level of work engagement of frontline employees even though these employees experience customer incivility.